A High Throughput Lab-On-A-Chip System for Label Free Quantification of Breast Cancer Cells under Continuous Flow. (2017) - Aslan, M.K.; Yalcin, Y. Demircan; Ozgur, E.; Gunduz, U.; Eminoglu, S.; Kulah, H.; Akin, T.
Abstract: This paper presents an LOC system combining microfluidic DEP channel with a CMOS image sensor for label and lens free detection and real-time counting of MCF-7 cells under continuous flow. Trapped and then released MCF-7 cells are accurately detected and counted under flow with a CMOS image sensor integrated underneath the DEP channel, for the first time in the literature. CMOS image sensor can capture 391 frames per second (fps) that allows detection of the released cells flowing through the channel with a flow rate up to 130 μl/min (0.468 m/s). Therefore, the proposed system is able to detect the cells under high flow where conventional techniques for cell quantification such as fluorescent tagging become unusable. Detected cells are automatically counted with a computer program and the counting accuracy of the whole system is 95%.